Effect of nitrogen and phosphorus application on agricultural soil food webs. Issue 8 (3rd July 2017) - Sun, Feng; Tariq, Akash; Chen, Huai; He, Qiongjie; Guan, Yixin; Pan, Kaiwen; Chen, Siyu; Li, Jiangtao; Zhao, Cancan; Wang, Hao; Gu, Yanfang
ABSTRACT: Aim of the present research is to investigate the effect of nitrogen (N) and phosphorus (P) on soil food webs (microbes, nematodes and microarthropods) trophic interactions in agriculture ecosystems. A complete randomized block design experiment of N and P fertilization was initiated in 2010 with four treatments: (1) P-addition, (2) N-addition, (3) NP-addition and (4) control. After 4 years of fertilization, compared with control, N-addition had a negative effect on microarthropods and clarify indirectly by significantly ( P < 0.05) increasing soil total nitrogen (0.37 g kg −1 ) and available nitrogen (20.03 mg kg −1 ). The reduction in microarthropods resulted significant ( P < 0.05) increase in bacterivores and fungivores feeding on bacteria and fungi, an example of top-down control. P-addition had indirect negative effects on microarthropods by means of significantly ( P < 0.05) increasing soil total phosphorus (0.62 g kg −1 ) and available phosphorus (24.17 mg kg −1 ), aggravated fungivores feeding on fungi and strengthened top-down control. NP-addition significantly ( P < 0.05) increased total microbial biomass, nematodes and microarthropods and resulted in bottom-up control. These results suggested that top-down effects were the dominant force in N- or P-addition treatments. NP-addition strengthened bottom-up control by enriching food resource. Unbalance fertilization could pose adverse on agricultural soil ecosystem and yield potential of crops.